Thyroid Hormone Function in the Rat Testis - Gao, Ying; Lee, Will M.; Cheng, C. Yan (Frontiers in Endocrinology, 2014)
Thyroid hormones are emerging regulators of testicular function since Sertoli, germ and Leydig cells are found to express thyroid hormone receptors. These testicular cells also express deiodinases which are capable of converting the pro-hormone T4 to the active thyroid hormone T3, or inactivating T3 or T4 to a non-biologically active form. Furthermore, thyroid hormone transporters are also found in the testis. Thus, the testis is equipped with the transporters and the enzymes necessary to maintain the optimal level of thyroid hormone in the seminiferous epithelium, as well as the specific thyroid hormone receptors to execute thyroid hormone action in response to different stages of the epithelial cycle of spermatogenesis. Studies using genetic models and/or goitrogens (e.g., PTU (propylthiouracil)) have illustrated a tight physiological relationship between thyroid hormone and testicular function, in particular Sertoli cell differentiation status, mitotic activity, gap junction function and blood-testis barrier (BTB) assembly. These findings are briefly summarized and discussed herein.